The informativeness and ability of independent multi-firm directors - Cook, Douglas O.; Wang, Huabing (Barbara) (Journal of Corporate Finance, 2011)
Motivated by SEC regulations requiring a majority of independent directors on corporate boards, we examine director informativeness and ability by observing the trading performance of independent directors who serve on multiple boards. As a proxy for informativeness, we find positive trading performance relative to purchases and sales. More impressive, these performance opportunities appear to be available to market participants who observe directors' Form 4 trades. We do not find evidence that diversification motives or busyness affects director trading performance. On the other hand, we do find that audit and compensation committee memberships enhance director trading performance on the sales side but that committee membership does not affect the profitability of director purchases. In comparison, multi-firm directors out-perform single-firm directors and this performance differential seems to be more attributable to superior ability than to better information.